The Ameliorative Effects of Ferulic Acid against Methotrexate Induced Testicular Damage in Rats - Ghada A. Taqa (Journal of applied veterinary sciences, 2025)
Nociceptive pain due to surgery is associated with discomfort and suffering. Metamizole sodium, though a potent analgesic, has been banned in many countries. The study is aimed at evaluating the analgesic efficacy of metamizole-sodium in castrated indigenous Nigerian dogs using electrocardiography (ECG). Twelve indigenous Nigerian male dogs aged between 6 months and 1 year with a mean body weight of 11.66 ± 1.26 kg undergoing castration were divided into three groups of four (4) animals each (n = 4). Groups A and B were treated with metamizole sodium via intramuscular (I/M) and transdermal routes at 50 mg/kg and 150 mg/kg, respectively. Group C was treated with normal saline 5 mg/kg i.m.Patients were monitored using standard methods for neutrophil count, vital parameters (rectal temperature, respiratory rate, heart rate and blood pressure), and ECG at 10 minutes before, during and at every 6-hour interval of 48 hours post-surgery. The neutrophil count in the intramuscular group (2.91 ± 0.55 × 109 L-1) was relatively lower than in the transdermal (3.54 ± 0.61 × 109 L-1) and control groups (4.41 ± 1.25 × 109 L-1) at 48 h post-surgery. There was no significant difference in the values of vital parameters obtained between the groups. The QRS interval was lower for intramuscular (0.10 ± 0.06 s) and transdermal (0.04 ± 0.00 s) than the control group (0.20 ± 0.16 s) at 18 h post-surgery. The P and T amplitudes were significantly (P < 0.001) higher for the tested groups than the control group during surgery and at 12 h post-surgery, respectively. In conclusion, the administration of metamizole sodium via the transdermal route prevented the side effect of agranulocytosis, evident by the decrease in neutrophil count of the intramuscular group compared to the transdermal group. Metamizole sodium transdermal patch induced analgesia, evident by the increase in QRS interval and decrease in P and T amplitudes of the ECG reading. This may be beneficial in alleviating pain due to castration in Nigerian indigenous dogs.Methotrexate (MTX), an extensively used chemotherapeutic and immunosuppressive agent, is well-documented for its gonadotoxic effects. Ferulic acid (FA), a natural phenolic compound with potent antioxidant properties, has shown protective effects in various organ systems. This study aimed to assess the protective and therapeutic potentials of FA against MTX-induced testicular damage in a rat model. Twenty-four adult male rats were allocated into four groups: control, MTX-only, MTX plus FA (protective), and MTX followed by FA (therapeutic). Testicular tissues were assessed histologically for tubular integrity and germ cell preservation. Histomorphometric parameters, including seminiferous tubule diameter and germinal epithelial height. Also, the level of Caspase-3 expression was analyzed using immunohistochemistry to examine apoptosis activity. The group treated with MTX showed testicular damageand a significant decrease in germ cells along with lower histomorphometric measures and increased Caspase-3 expression levels. On the other hand, both groups treated with FA displayed noticeable improvements in both histology and molecular aspects. The treated group showed normal testicular structure, along with restored histomorphometric values and minimal Caspase-3 expression similar, to the control group. Conclusion: FA successfully reduced the effects of (MTX) in the testicles by maintaining their structure and preventing cell death processes. This suggests that FA could be an addition to protect men’s reproductive health during chemotherapy treatments